Reliable data recovery from errors due to noisy channel during transmission - Yong, Chung How (Nanyang Technological University, 2023)
Error correction codes (ECCs) are a fundamental component of modern communication and data storage systems. These codes add redundancy to transmitted or stored data to enable detection and correction of errors that may occur during transmission or storage. ECCs are widely used in many applications and the choice of ECC depends on the specific application and the trade-offs between error-correcting capability, complexity, and resource requirements.